2021
DOI: 10.3389/fpsyg.2021.569065
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Personality and Social Support With Pre-retirement Anxiety: Mediating Role of Subjective Career Success

Abstract: The main objective of this paper is to investigate the mediating role of subjective career success (SCS) in the relationship between proactive personality, social support (SS), and pre-retirement anxiety. Using a two-wave longitudinal design, 624 pre-retirees were sampled (M = 56.49 years; SD = 4.56); of these, 237 (37.98%) were males and 387 (62.02%) were females. Measurement model and mediation test were performed using the SmartPLS and IBM SPSS Amos software. The result indicated that proactive personality,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 107 publications
(129 reference statements)
0
14
0
Order By: Relevance
“…However, studies have attested to the prevalence of retirement anxiety among different categories of employees,[ 2 3 7 ] very few of these studies considered different dimensions of retirement anxiety together. [ 8 9 10 ] According to statistics, retirement anxiety occurs in different dimensions, but three major areas have been identified. [ 8 11 12 ] Particularly, studies investigating retirement anxiety have identified the social detachment dimension as concerns relating to the perception and attitude of employees to loss of social connections or change in the social cycle due to retirement.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, studies have attested to the prevalence of retirement anxiety among different categories of employees,[ 2 3 7 ] very few of these studies considered different dimensions of retirement anxiety together. [ 8 9 10 ] According to statistics, retirement anxiety occurs in different dimensions, but three major areas have been identified. [ 8 11 12 ] Particularly, studies investigating retirement anxiety have identified the social detachment dimension as concerns relating to the perception and attitude of employees to loss of social connections or change in the social cycle due to retirement.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 9 10 ] According to statistics, retirement anxiety occurs in different dimensions, but three major areas have been identified. [ 8 11 12 ] Particularly, studies investigating retirement anxiety have identified the social detachment dimension as concerns relating to the perception and attitude of employees to loss of social connections or change in the social cycle due to retirement. [ 8 11 ] In a related development, another study identified the role of health and income-related concerns, loss of work-related identity, and changes in social connections on retirement anxiety among university academicians[ 9 ] while Szinovacz et al .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations